2010
DOI: 10.1371/journal.pone.0011478
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Obligate Intracellular Gamma-Proteobacterium Associated with Ixodid Ticks, Diplorickettsia massiliensis, Gen. Nov., Sp. Nov

Abstract: BackgroundObligate intracellular bacteria of arthropods often exhibit a significant role in either human health or arthropod ecology.Methodology/Principal FindingsAn obligate intracellular gamma-proteobacterium was isolated from the actively questing hard tick Ixodes ricinus using mammalian and amphibian cell lines. Transmission electron microscopy revealed a unique morphology of the bacterium, including intravacuolar localization of bacteria grouped predominantly in pairs and internal structures composed of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 25 publications
0
57
0
2
Order By: Relevance
“…However, phylogenetic analyses of sequence data of the 16S rRNA gene subsequently revealed that Rickettsiella grylli represented a sister taxon to two genera of Gammaproteobacteria: Coxiella and Legionella (12). As a consequence, the genus Rickettsiella was transferred from the Rickettsiales to the family Coxiellaceae within the order Legionellales (20), a placement that has been supported by other molecular studies (11,(21)(22)(23)(24)(25)(26)(27)(28)(29). Rickettsiella have been reported in a diverse range of arthropod hosts, including insects (e.g., beetles, flies, crickets, locusts, cockroaches, wasps, midges, moths, and aphids), collembolans, crustaceans (e.g., isopods and crabs), and arachnids (e.g., spiders, scorpions, ticks, and mites) (20,30).…”
mentioning
confidence: 73%
“…However, phylogenetic analyses of sequence data of the 16S rRNA gene subsequently revealed that Rickettsiella grylli represented a sister taxon to two genera of Gammaproteobacteria: Coxiella and Legionella (12). As a consequence, the genus Rickettsiella was transferred from the Rickettsiales to the family Coxiellaceae within the order Legionellales (20), a placement that has been supported by other molecular studies (11,(21)(22)(23)(24)(25)(26)(27)(28)(29). Rickettsiella have been reported in a diverse range of arthropod hosts, including insects (e.g., beetles, flies, crickets, locusts, cockroaches, wasps, midges, moths, and aphids), collembolans, crustaceans (e.g., isopods and crabs), and arachnids (e.g., spiders, scorpions, ticks, and mites) (20,30).…”
mentioning
confidence: 73%
“…The European sheep tick Ixodes ricinus is the most prevalent tick species in central Europe and is known to vector a number of human and animal pathogens such as Borrelia spp., Rickettsia helvetica, Rickettsia monacensis, Anaplasma phagocytophilum, Ehrlichia spp., Francisella tularensis, and others (55). Recently, a novel endocellular gammaproteobacterium was isolated from I. ricinus using mammalian and amphibian cell lines, which was allied to insect endosymbionts and pathogens of the genus Rickettsiella in the order Legionellales and was designated Diplorickettsia massiliensis (56). A large-scale serological survey detected three Diplorickettsia-positive cases of over 13,000 human serum samples (57), indicating its potential relevance to human health.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, growth of R. felis in Drosophila melanogaster S2 cells was reported, with a cell infection rate of 100% after 19 days of incubation at 25°C (331). Other arthropod-borne bacteria, such as Diplorickettsia massiliensis (332), Wolbachia sp., and Bartonella bacilliformis (40), as well as other bacteria such as Piscirickettsia salmonis (333) and M. ulcerans (334) can also be cultivated more effectively by using this cell line.…”
Section: Cell Culturementioning
confidence: 99%